Diffusion-Weighted Magnetic Resonance for Assessing Ileal Crohn's Disease Activity. Issue 9 (13th July 2014) - Caruso, Antonino; D'Incà, Renata; Scarpa, Marco; Manfrin, Paolo; Rudatis, Massimo; Pozza, Anna; Angriman, Imerio; Buda, Andrea; Sturniolo, Giacomo Carlo; Lacognata, Carmelo
Abstract : Background: Endoscopy and imaging objectively assess Crohn's disease (CD) activity. Magnetic resonance enterography (MRE) uses no ionizing radiation, carries no significant morbidity, and is highly sensitive in revealing soft tissues inflammation. Diffusion-weighted imaging can distinguish intestinal inflammation from a lower diffusion of water molecules giving rise to a reduced apparent diffusion coefficient. The magnetic resonance index of activity score and, more recently, the Clermont score were recently developed for staging CD activity. The aim of this study was to compare the MRE scores and the Simple Endoscopic Score for CD in identifying ileal CD activity. Methods: Fifty-five patients with ileal and ileocolonic CD were consecutively enrolled between June 2012 and June 2013. All patients underwent clinical examination, biochemical tests, MRE, and colonoscopy to assess disease activity. Results: MRE assessed active ileal disease in 31 patients (56.3%). The Clermont score significantly correlated with the magnetic resonance index of activity score (r = 0.91; P < 0.0001) and the Simple Endoscopic Score for CD (r = 0.76; P < 0.0001). The apparent diffusion coefficient correlated with the Simple Endoscopic Score for CD (r = −0.63; P < 0.0001) especially in unoperated patients. Conclusions: The Clermont score and the apparent diffusion coefficient value can stage ileal CD, avoiding the need to use contrast agents.